Characterization of natives starches and their effect on physical properties of water-based drilling fluids (Nexo Revista Científica, 2024)
The purpose of the research was to compare the functional properties of five starches (ocumo, cassava, mapuey, congo yam and bitter cane) developed at the university and to determine their effect when used as filter controllers on the physical properties of a water-based fluid. During the study of the functional properties, good amylose content was detected in the starches, necessary for the good performance of drilling fluids, acid pH characteristic of natural starches and good performance for water adsorption. The formulated fluids presented good rheology and filtering less than ten for the ocumo, cassava and sour cane starches. The opposite was the case of mapuey and congo yam starches, whose values were higher than ten. The factorial design showed significant statistical differences between the starches (blocks) with respect to the commercial one, but not between it and sour cane starch. Likewise, there were statistical differences between the physical properties of the starches with the commercial one, except for sour cane starch, which only differed in filtering compared to the commercial one. Despite the results, the other fluids are not ruled out, because their use depends on the drilling operating conditions.